Administrative Trends in U.S. Dental Schools. Issue 11 (1st November 2014) - Fu, Martin M.; Rodriguez, Angel; Chen, Rebecca Y.; Fu, Earl; Liao, Shu‐Yi; Karimbux, Nadeem Y.
Abstract : The aims of this study were to analyze the administrative trends in U.S. dental schools at the beginning and end of a thirteen‐year period and to identify the predictive factors for those changes. Administrative trends were measured by the difference in the number of major administrative positions for 1997 and 2010 reported in American Dental Education Association (ADEA) and American Dental Association (ADA) publications. Secondary measures (program length, student enrollment, and tuition) were also gathered. The mean numbers of administrative positions per school significantly increased over the study period, while the mean number of clinical science departments per school significantly decreased. The change in the number of directors was positively correlated with the change in student enrollment, but inversely correlated with the change in number of vice/associate/assistant deans. The change in the number of clinical science departments was positively correlated with changes in student enrollment and out‐of‐state tuition, but inversely correlated with the change in in‐state tuition. The number of all departments per U.S. dental school significantly decreased in this period. The schools that had consolidation of clinical science departments were less likely to have increases in student enrollment and out‐of‐state tuition, but more likely to have increases in in‐state tuition.